ChemInform Abstract: Silk Structure Studied with Nuclear Magnetic Resonance. Issue 24 (2nd June 2014) - Asakura, Tetsuo; Suzuki, Yu; Nakazawa, Yasumoto; Yazawa, Koji; Holland, Gregory P.; Yarger, Jeffery L.
Abstract Review: 196 refs.